Promoting Access to Justice through the Broadcasting of Legal Proceedings - Mokoena, Kgomotso; Koen, Louis (Potchefstroom Electronic Law Journal, 2022)
This article considers a lack of legal literacy as a barrier to access to justice. The article then considers the potential effectiveness of introducing media-based teaching tools to South African society in an attempt to increase the rights awareness of South Africans. In so doing, the article proposes ways in which this improved rights awareness can assist South Africans to engage with the law, their rights, and the judicial system as a whole in a manner which promotes improved access to justice. It considers television-based teaching tools already implemented in the country as well as possible future interventions. It draws on past television-based education initiatives in South Africa in an effort to consider how South Africans engage with television-based teaching tools. It further draws on the open justice principle to argue for the increased broadcasting of legal proceedings. The article then considers television in three other jurisdictions and undertakes an assessment of the effect of television on our cognitive and subliminal engagement with the law. The discussion on other jurisdictions includes how fictional legal programming, syndicated court programmes as well as other forms of "Court TV" have contributed both positively and negatively to the legal consciousness of those societies.